Well-posedness, global existence and blow-up phenomena for an integrable multi-component Camassa–Holm system. (September 2016) - Zhang, Zeng; Yin, Zhaoyang
Abstract: This paper is concerned with a new integrable multi-component Camassa–Holm system, which has been proven to be integrable and has peakon solutions. This system includes many one-component and two-component Camassa–Holm type systems as special cases. In this paper, we first establish the local well-posedness and a continuation criterion for the system, then we present several global existence and blow-up results for two important integrable two-component subsystems. Our obtained results cover and improve considerably recent results in Gui et al. (2013), Yan et al. (2015).